2016
DOI: 10.1103/physreve.94.042805
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph selection and nucleation pathway in the crystallization of Hertzian spheres

Abstract: The crystallization process of Hertzian spheres is studied by means of molecular dynamics simulations in an NPT ensemble where the total number of particles N, the pressure P, and the temperature T are kept constant. It has been observed that the bond orientational ordering rather than the translational ordering (density) plays a primary role. The crystal polymorphs are determined by the state points. Under the conditions of small supercooling, the system is likely to be nucleated into crystals that have a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…As a fundamental process of crystallization, the formation of precursors has been observed in various systems. 4,[8][9][10][11][12][13]16,17 In the picture of precursor-mediated crystallization, precursors act as the seeds of nucleation. Before the nucleation takes place, some clusters of precursors appear first in the system.…”
Section: A Precursor Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…As a fundamental process of crystallization, the formation of precursors has been observed in various systems. 4,[8][9][10][11][12][13]16,17 In the picture of precursor-mediated crystallization, precursors act as the seeds of nucleation. Before the nucleation takes place, some clusters of precursors appear first in the system.…”
Section: A Precursor Formationmentioning
confidence: 99%
“…7). As previous studies have suggested that there are correlations between the location of critical nucleus and Q 6 order parameter, 13,16,18,20,31 we define the liquid particles with the character of Q 6 ≥ 0.3 as the precursors. Notice here that the threshold of Q 6 for precursors is just chosen arbitrarily, and that it can of course be chosen as other values (e.g., 0.28 and 0.29) close to 0.3.…”
Section: A Precursor Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…FCC-like particles are those withw 6 ≤ 0 and w 4 ≤ 0. This useful assignment criteria to distinguish different solid-like local environments in the metastable fluid phase has been used extensively in computer simulations of model atomic and molecular systems [47][48][49][50].…”
Section: B Nucleation Free Energy Barrier and Polymorph Selectionmentioning
confidence: 99%